Razmerje med skokom z nasprotnim gibanjem in skokom iz počepa - Pleša, Jernej (Šport (Ljubljana), 2022)
Jumping power is usually evaluated through different variables of squat jump (SJ) and countermovement jump (CMJ). Besides the basic output parameters of CMJ and SJ, practitioners might be interested in calculating the ratio between the jumps, which is termed as “eccentric utilization ratio” (EUR). Traditionally, it was believed that higher values of EUR reflect better efficiency in elastic energy storage, which is expected to have a positive impact on athletic performance. However, later studies have shown that EUR does not correlate with sport performance and that while a higher values of EUR can be consequence of superior CMJ performance, it can also reflect poorer SJ performance. Poor SJ performance (relative to CMJ) can reflect excessive muscle slack and poor ability to develop force rapidly, thus not necessary reflect better efficiency in storage of elastic energy. Jump height primarily depends on force impulse, therefore, the ability to rapidly produce force is crucial for SJ performance. In addition, the literature reports that higher values of EUR may be due to differences in kinematics between the jumps (e.g. squat depth and torso lean), as well as the consequence of movement coordination, as it has been stressed that SJ is an unnatural movement, since most high-force ballistic actions are typically performed with a certain amount of countermovement. In addition to the underlying mechanisms of EUR, this paper also reviews recent findings of cross-sectional and interventional studies that point against using EUR in sports practice.
Keywords: energija; skoki; šport; športniki